2011
DOI: 10.1126/science.1198767
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Phage Antagonistic Coevolution in Soil

Abstract: Bacteria and their viruses (phages) undergo rapid coevolution in test tubes, but the relevance to natural environments is unclear. By using a "mark-recapture" approach, we showed rapid coevolution of bacteria and phages in a soil community. Unlike coevolution in vitro, which is characterized by increases in infectivity and resistance through time (arms race dynamics), coevolution in soil resulted in hosts more resistant to their contemporary than past and future parasites (fluctuating selection dynamics). Fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
372
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 412 publications
(412 citation statements)
references
References 26 publications
28
372
6
Order By: Relevance
“…Some of the prime experimental models are bacteria and their lytic phages, which exhibit rapid evolution and are amenable to time-shift tests. Recent study indicates that coevolving populations may exhibit either ARD or FSD (12,(21)(22)(23)(24), and there is some evidence for the genetic mechanism involved [e.g., mutations at tail fiber genes (12,25)] and for the expansion of the phage host range as coevolution proceeds (6). Most studies of bacteria-phage coevolution involve the model system Pseudomonas fluorescens SBW25 and its lytic phage ϕ2 (15).…”
mentioning
confidence: 99%
“…Some of the prime experimental models are bacteria and their lytic phages, which exhibit rapid evolution and are amenable to time-shift tests. Recent study indicates that coevolving populations may exhibit either ARD or FSD (12,(21)(22)(23)(24), and there is some evidence for the genetic mechanism involved [e.g., mutations at tail fiber genes (12,25)] and for the expansion of the phage host range as coevolution proceeds (6). Most studies of bacteria-phage coevolution involve the model system Pseudomonas fluorescens SBW25 and its lytic phage ϕ2 (15).…”
mentioning
confidence: 99%
“…While there is considerable evidence for coevolutionary arms races taking place among bacteria and phages (Bohannan and Lenski 2000;Buckling and Rainey 2002a;Mizoguchi et al 2003;Brockhurst et al 2006;Forde et al 2008;Scanlan et al 2011) and various other host-parasite systems (Little et al 2006;Schulte et al 2010), there is limited evidence of fluctuations in range except for some plantfungus interactions (e.g., Thrall and Burdon 2003). Recent work with Pseudomonas fluorescens and lytic phages has shown that fluctuating selection between genotypes with similar ranges is possible, either following or in the absence of a coevolutionary arms race (Gomez and Buckling 2011). In addition, the frequent occurrence of local adaptation indicates that there may be multiple routes to generalism (Buckling and Rainey 2002b;Morgan et al 2005;Vos et al 2009;Koskella et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Continuous supply and migration of resistant bacteria from biofilms would have then likely increased the proportion of resistant bacteria also in planktonic populations leading to nonobservable coevolutionary dynamics. It has also been shown that spatially structured soil environments could favour fluctuating coevolutionary dynamics and local phage–bacteria adaptation in time (Gomez & Buckling, 2011), while spatial structure could decrease bacteria–phage encounter rates leading to slower rate of coevolution (Brockhurst et al., 2006). In future, it would be interesting to test directly how the absence and presence of spatial refugees affect the host–parasite coevolutionary dynamics.…”
Section: Discussionmentioning
confidence: 99%